Iono-Covalent Character of the Metal–Oxygen Bonds in Oxides: A Comparison of Experimental and Theoretical Data. (2004) - Lenglet, M.
Abstract : The aim of this paper is to review the actual data on the chemical bond in binary and mixed oxides. The electronegativity( χ M ) and the acidityp a scales are the most significant semi-empirical concepts for predicting the trend of bonding character in iono-covalent oxides. A satisfactory correlation between the data issued from the acidity scale and the calculated ionic charges has been established. The most recent studies show that the hybrid methods such as the B3LYP method lead to more reliable results for the description of structural, energetic and electronic properties of binary oxides than those from standard methods.